An examination of the factors in the policy enabling environment that influence the formulation and implementation of harm reduction policy in Thailand - Cole, Michael John (Curtin University, 2017)
This research study identified and analysed the major national, regional and international factors which influenced Thai drug policy formulation and implementation. A qualitative inductive theoretical process incorporating different sources of data (interrogation of the literature, expert interviews and a survey) is used. Data were examined through political economy analysis and other relevant policy analysis frameworks. The results showed the important role of key institutions and the influence of central paradigms, ideologies and cultural values.